1948
DOI: 10.1104/pp.23.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Deficiency and Excess in Guayule I. Growth Responses and Mineral Content

Abstract: The extensive literature dealing with the role of potassium in plant metabolism has been reviewed by HOFFER (20), by various authors (47) in a recent symposium and in several reviews on mineral nutrition of plants (11,17,18,28,39,46). Very recently SIDERIS and YOUNG (42,43,44) have dealt with several aspects of the problem. HOAGLAND (19) has pointed out that at one time or another a role in almost every important physiological process in the plant has been ascribed to potassium. Yet, the mechanism of its role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1948
1948
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Effects of different rates of potassium supply upon the growth anid mineral contents of guayule plants have been reported in a previous publication (5). It was noted that although the nutrient treatments resulted in large differences in concentrations of potassium and other cations within the plants, the total milliequivalents of cations per 100 grams of dry tissue for the whole plants was nearly the same for all treatments.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Effects of different rates of potassium supply upon the growth anid mineral contents of guayule plants have been reported in a previous publication (5). It was noted that although the nutrient treatments resulted in large differences in concentrations of potassium and other cations within the plants, the total milliequivalents of cations per 100 grams of dry tissue for the whole plants was nearly the same for all treatments.…”
mentioning
confidence: 69%
“…Sodium was determined in the dried leaves samples (5). In some cases, dried samples were also employed for determination of potassium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These workers have also shown that of the total free reducing sugars, the amounts of free nion-fructose sugars are always greater than the amounits of free fructose in spite of the fact that the chief reserve carbohydrates in guayule are polymers of fructose, levulins and inulin. The coniditions of the present experiment were not conducive to large accumulations of inulin, or higher polymer levulins, insofar as the experiment consisted of a phase of rapid growth.So far as the writers are aware, no detailed study has been made of the nitrogenous fractions in guayule.Effects of potassium supply upon growth responses and mineral contents of guayule plants and upon cation and inorganic and organic aniion contents of the leaves have been reported (8,9). In this paper are considered carbohydrate and nitrogenous fractions in tissues of the same plants.…”
mentioning
confidence: 99%